2023
DOI: 10.1002/dc.25144
|View full text |Cite
|
Sign up to set email alerts
|

Usefulness of cytological diagnosis in pancreatic endoscopic ultrasound‐guided fine needle aspiration or biopsy: Comparison with histological diagnosis and relationship with puncture route and sample acquisition method

Abstract: Background The purpose of this study was to clarify the role of cytology when using endoscopic ultrasound‐guided fine needle aspiration or biopsy (EUS‐FNA/FNB) for pancreatic lesions by comparison with histology, and also to examine differences in diagnostic accuracy depending on the puncture route and sample acquisition method. Methods We studied 146 cases in which cytology and histology were performed when undertaking pancreatic EUS‐FNA/FNB and the final histological diagnosis was obtained from surgically re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

2
0
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 31 publications
2
0
0
Order By: Relevance
“…Accuracy provided by both methods was also satisfactory – 89.5% (±11.7; 63.0–100.0) for FNA and in the FNB group 90.8% (±7.1; 77.0–100.0)—again with no statistical difference (Figure 2). These data show no superiority of FNB over FNA in terms of diagnosis capability, finding consistent with other studies in the literature 9,10,35 . As a matter of fact, studies that compared FNA in association with FNB to FNA or FNB alone concluded that the association of both methods held better diagnostic yield and accuracy than any of the isolated techniques 18,35 .…”
Section: Discussionsupporting
confidence: 88%
See 1 more Smart Citation
“…Accuracy provided by both methods was also satisfactory – 89.5% (±11.7; 63.0–100.0) for FNA and in the FNB group 90.8% (±7.1; 77.0–100.0)—again with no statistical difference (Figure 2). These data show no superiority of FNB over FNA in terms of diagnosis capability, finding consistent with other studies in the literature 9,10,35 . As a matter of fact, studies that compared FNA in association with FNB to FNA or FNB alone concluded that the association of both methods held better diagnostic yield and accuracy than any of the isolated techniques 18,35 .…”
Section: Discussionsupporting
confidence: 88%
“…These data show no superiority of FNB over FNA in terms of diagnosis capability, finding consistent with other studies in the literature 9,10,35 . As a matter of fact, studies that compared FNA in association with FNB to FNA or FNB alone concluded that the association of both methods held better diagnostic yield and accuracy than any of the isolated techniques 18,35 . This is probably explained by the distinct type of information provided by cytology and histology, empowered when combined (Figure 3).…”
Section: Discussionsupporting
confidence: 87%